In vitro characterization of beta-cyclodextrin liposomal formulation of cisplatin nanomedicine - Panijapatr Wasubhadtanasaka (Precision Nanomedicine)
This study aims to develop a nanomedicine-based approach to protect healthy tissue during cancer treatment, improve patient compliance, reduce adverse drug reactions, and enhance the quality of life. By utilizing hydroxypropyl-β-cyclodextrin (BPCP) to increase drug hydrophilicity and liposomes for controlled release of cisplatin (CP), the hydroxypropyl-β-cyclodextrin-cisplatin liposomal formulation (BCDCPLP) demonstrated improved stability, targeted delivery, and reduced toxicity. The study confirmed that the above formulation had the highest cytotoxicity against HeLa cells, with significantly lower IC50 and IC90 values than cisplatin alone. This is attributed to improved drug stability and cellular uptake. Caspase-3 and cleaved PARP assays confirmed that BCDCPLP and CP-loaded liposomes induced substantial apoptosis, with BCDCPLP showing the highest increase in caspase-3 activity and PARP cleavage at 85 kDa. The ability of BCDCPLP to enhance apoptosis was further demonstrated through Western blot analysis, where the density of PARP cleavage bands was highest in BCDCPLP-treated cells, followed by CPLP and CP-treated cells. The study highlights that the cumulative release of PARP from CP-nanocarrier complexes leads to more efficient apoptosis than free CP. These findings align with the synergistic effects observed when combining CP with PARP inhibitors, which induce mitochondrial membrane permeabilization and cytochrome C release, activating the intrinsic apoptosis pathway. The potential of these nanomedicines, especially BCDCPLP, is in reducing the required dosage while maintaining therapeutic efficacy offers promising advances in cancer therapy.